Repeated cobalt and chromium ion measurements in patients with large-diameter head metal-on-metal ReCap-M2A-Magnum total hip replacement - Mäntymäki, Heikki; Lankinen, Petteri; Vahlberg, Tero; Reito, Aleksi; Eskelinen, Antti; Mäkelä, Keijo (Acta Orthopaedica, 2019)
Background and purpose — Whole blood (WB) cobalt (Co) and chromium (Cr) ion levels have a major role in the follow-up of metal-on-metal total hip replacement (MoM THR). We investigated, first, if there was a change in WB Co or Cr levels over repeated measurements in patients with ReCap-M2A-Magnum THR, and, second, determined how many patients had WB Co or Cr levels that exceeded the safe upper limits (SUL) in the repeated whole blood metal ion assessment. Patients and methods — A Recap-M2A-Magnum THR was used in 1,329 operations (1,188 patients) at our institution between 2005 and 2012. We identified all patients (n = 319) with unilateral ReCap-M2A-Magnum implants who had undergone at least 2 repeated metal ion measurements with the first blood sample taken mean 5.5 years (1.8–9.3) after surgery and the second taken mean 2 years (0.5–3) after the first. Results — The median WB Co and Cr ion levels decreased in repeated measurements from 1.40 (0.40–63) ppb to 1.10 (0.20–68) ppb and from 1.60 (0.60–13.0) ppb to 1.10 (0.30–19.0) ppb, respectively. 7% of the Co ion values exceeded SUL at the initial measurement, and 7% at the control measurement. The proportion of Cr ion values exceeding the safe upper limit (SUL) decreased during the measurement interval from 5% to 4%. Interpretation — Repeated metal ion measurements in unilateral ReCap-M2A-Magnum patients in a mean 2-year time interval did not show any increase. Long-term ion levels are, however, not yet known.